2018
DOI: 10.1002/jbm.a.36518
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle and mesenchymal stem cells in bone regeneration: recent progress and perspectives

Abstract: Transplanting mesenchymal stem cells (MSCs) has been widely perceived as an ideal treatment for bone repair and regeneration, owing to their differential potential. However, researchers found that very few intravenous MSCs could stay in the target tissue, whereas the majority of them are trapped in liver, spleen, and lung, largely reducing its therapeutic effects. Recently, extracellular vesicles (EVs) have attracted increased attention due to their function in bone repair and advantages over traditional cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 99 publications
(113 reference statements)
0
26
0
1
Order By: Relevance
“…In bone regeneration, bone mesenchymal stem cells (BMSCs) are considered promising seed cells for tissue engineering applications, especially due to their excellent potential for differentiation into osteoblasts, chondrocytes, adipocytes, neurons, and other cell types. 12,13 The outcomes of BMSC proliferation and differentiation are highly influenced by the surrounding environment. 14 Nanomaterials play significant roles in determining the fate of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In bone regeneration, bone mesenchymal stem cells (BMSCs) are considered promising seed cells for tissue engineering applications, especially due to their excellent potential for differentiation into osteoblasts, chondrocytes, adipocytes, neurons, and other cell types. 12,13 The outcomes of BMSC proliferation and differentiation are highly influenced by the surrounding environment. 14 Nanomaterials play significant roles in determining the fate of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that bioactive molecules, such as IGF-1, TGF-β, vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), angiogenin, and IL-6 that are derived from MSCs, can support bone regeneration to a great extent [ 173 , 174 , 175 , 176 ]. Furthermore, exosomes released by MSCs have been demonstrated to have a promising effect on bone remodeling and the prevention of bone loss in vivo [ 177 , 178 ].…”
Section: Therapeutic Approach and Novel Strategiesmentioning
confidence: 99%
“…To date, there have been an increasing number of studies of biomaterial-mediated EV therapies, in which diverse scaffolds with modifications of their properties have shown great potential for loading and controlling the release of EVs. Although several recent reviews have focused on EV application in tissue regeneration as well as the involved mechanisms of EVs (Chen et al, 2017;Silva et al, 2017;Taverna et al, 2017;Keshtkar et al, 2018;Li Q. et al, 2018;Chu et al, 2019), our review specifically focuses on the controlled release of EVs loaded in scaffolds and provides a discussion of the existing and potential modifications of EVs delivery systems for BTE (Figure 1).…”
Section: Introductionmentioning
confidence: 99%